Developing Digital Worksheet for Teaching Reading Comprehension to Grade XI Students of Automotive Department at SMKN 5 Medan - Nia Febriyanti; Indra Hartoyo (Universitas Negeri Medan, 2025)
The aim of this study was to develop digital worksheet for teaching reading comprehension to grade XI students of Automotive Department at SMKN 5 Medan. This study was conducted using Research and Development (R&D) method from Gall, Gall, and Borg (2003) under six stages; gathering data and information, analyzing the data, media design, validating by experts, revising the media, and final product. The subject of the study was the eleventh-grade students of Automotive Department at SMKN 5 Medan, specifically in class XI TKRO 4. There were 30 students who participated in this research. The data were collected through questionnaire and documentation. The results of the study showed that Quizizz platform can be used as students’ reading comprehension worksheet. In the percentage form, the average score of experts’ validation in terms of product and content aspect was 94.2%, the process aspect was 90%, the linguistic aspect was 100% and the layout aspect was 100%. The scores were categorized as “Very Good”. It means the developed digital reading worksheet of Descriptive Text and Procedure Text was valid and appropriate to be used as reading worksheet for the eleventh-grade students of Automotive Department at SMKN 5 Medan.